Polymers with Nano-Encapsulated Functional Polymers: Encapsulated Phase Change Materials. Encapsulated Phase Change Materials. - Tebaldi, Marli Luiza; Belardi, Rose Marie; Montoro, Sérgio Roberto [UNESP] (Elsevier, 2015)
Nowadays fossil fuels are dominating the world energy market, but due to their finite reserves and their high usage have increased attention to seek new alternatives and to reduce their consumption. One of the most important technologies is the thermal energy storage. Phase change materials (PCMs) are materials that present high solar thermal-energy storage capacity, high latent heat of transition, high energy densities and low cost. PCMs can be formulated from a wide variety of materials including natural and synthetic polymers. These materials can be encapsulated with a series of purposes, such as increasing the rate of heat transfer and increasing thermal and mechanical stability. Although PCMs can be encapsulated at macro, micro, and nanoscales, only macro and micro capsules have been commercialized by different industries, whereas the nanoencapsulation is still limited to the laboratory level. The interest related to the encapsulation of PCMs on a nanoscale involves their better structural stability when compared to the macro and microcapsules.
Keywords: Encapsulated PCM; Energy storage; Phase change materials